Real estate taxation reform: Tax land values, abolish privileges - Stefan Bach; Sebastian Eichfelder (DIW Weekly Report, 2021)
Real estate is taxed at comparatively low rates in Germany, with primarily the affluent benefiting from numerous existing tax privileges. This Weekly Report describes the current state of real estate taxation in Germany and outlines reform proposals that could increase tax revenue, improve the efficiency of the tax system, and reduce wealth and income inequality. In the case of property tax, value-based taxation should be strengthened, which would double revenue in the longer term. Income tax should include all capital gains and tax avoidance opportunities for real estate investments should be restricted, in particular those using limited liability companies. With regard to inheritance tax, it would be advisable to no longer provide housing firms with preferential treatment. In the case of the real estate transfer tax, share deals and similar arrangements should be taxed equally; if necessary, first-time homebuyers could be given preferential treatment. All in all, tax revenue would increase by around 27 billion euros per year, or 0.7 percent of GDP, if such reforms were implemented. The additional revenue could be used to reduce the tax burden on earned income, especially for middle income households.
Keywords: H24; R31; D31; 330; Income and wealth taxation; housing and real estate markets; distribution of income and wealth